Periodic Solutions for Second Order Hamiltonian Systems with Impulses via the Local Linking Theorem. (10th July 2014) - Bao, Longsheng; Dai, Binxiang
Abstract : A class of second order impulsive Hamiltonian systems are considered. By applying a local linking theorem, we establish the new criterion to guarantee that this impulsive Hamiltonian system has at least one nontrivial T-periodic solution under local superquadratic condition. This result generalizes and improves some existing results in the known literature.